SOME SCRIBAL AND LINGUISTIC FEATURES OF THE GENESIS PART OF THE OLDEST PESHITTA MANUSCRIPT (B.M. ADD. 14425)1 - Wernberg-Møller, P. (Journal of Semitic studies, 1968)
P. WERNBERG-MØLLER; SOME SCRIBAL AND LINGUISTIC FEATURES OF THE GENESIS PART OF THE OLDEST PESHITTA MANUSCRIPT (B.M. ADD. 14425)1, Journal of Semitic Studies, V